Co-improving the electrocatalytic performance and H2S tolerance of a Sr2Fe1.5Mo0.5O6−δ based anode for solid oxide fuel cells. Issue 30 (21st July 2022) - Xu, Chunming; Zhang, Lihong; Sun, Wang; Ren, Rongzheng; Yang, Xiaoxia; Ma, Minjian; Qiao, Jinshuo; Wang, Zhenhua; Zhen, Shuying; Sun, Kening
Abstract : Ti-doping enhancing the ability of SFM to resist H2 S corrosion, the diffusion and surface adsorption process of oxygen and the reaction kinetics have been significantly improved. Abstract : Co-improving the structural stability and electrocatalytic activity of anode materials is a major challenge for the development of solid oxide fuel cells (SOFCs). Herein, a novel anode material Sr2 Fe1.5 Mo0.4 Ti0.1 O6− δ (SFMT) is designed and prepared by using Ti to replace Mo of Sr2 Fe1.5 Mo0.5 O6− δ (SFM). Ti doping effectively enhances the ability of SFM to resist H2 S corrosion and SFMT maintains the desired perovskite structure after being exposed to H2 S (1000 ppm). Moreover, the partial replacement of Mo 5+ /Mo 6+ by Ti 4+ ions can also improve the concentration of oxygen vacancies and enhance the oxygen ion surface exchange and bulk diffusion capabilities. The SFMT-based SOFC delivers an excellent power output in H2 containing 500 ppm H2 S and stably operates for a long time (>50 h), resulting in a maximum power density of 0.71 W cm −2 at 800 °C. The current study presents a promising material design strategy for developing high-performance SOFC anodes.